Physico-chemical characteristics of Pliek-U in Aceh. Issue 1 (1st December 2022) - Agustina, R; Hayati, R; Hasanuddin, H; Fadhil, R
Abstract: Indonesia is the one of the countries which has the richness of fermented food traditional such as Pliek-U. The natural coconut flesh was contain the components that physiologically beneficial. Nutritional quality from the meat coconut fruit were increased through the one of the fermentation processes for making the Pliek-U. This study was determine the proportion of content in Pliek-U whereas that was circulate in the community. The method for physico-chemical characteristics of Pliek-U was carried out in a laboratory using standard the basic formula. The results showed the percentage range of Pliek-U, it was obtained for 5.816-11.593% to the water content. Then, the fat content was found 34, 628 - 38.998%, whereas the protein content was known as 29, 164 - 34, 658%. However, the proportion of the ash content was 3.606 - 5.264%. The results from the Pliek-U sample have been reported the highest percentage of the carbohydrate content (22.548%), while the lowest is 13.952%. Furthermore, Pliek-U was contains to free fatty acids in the range of 2, 637 - 5, 589. Then, Pliek-U samples that ready to be served have a pH content in the range of 4.083-5.589%. The output test the quality parameters from the physical and chemical properties in Pliek-U can be used as a reference or standard for the quality of Pliek-U which has been circulating for years in the aceh community.